2020
DOI: 10.1007/s11914-020-00606-2
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing for Bone Regeneration

Abstract: Purpose of review:The purpose of this review is to illustrate the current state of 3D printing (3DP) technology used in biomedical industry towards bone regeneration. We have focused our efforts towards correlating materials and structural design aspects of 3DP with biological response from host tissue upon implantation. The primary question that we have tried to address is -can 3DP be a viable technology platform for bone regeneration devices?Recent findings: Recent findings show that 3DP is a versatile techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…FDM printing requires thermoplastic materials (linear macromolecules), but most pharmaceutical grade materials do not meet the requirements. An improved technology based on FDM, called fused deposition of ceramics (FDC), gets rid of the limitations of materials used [ 7 ].…”
Section: 3d Printing Techniquesmentioning
confidence: 99%
“…FDM printing requires thermoplastic materials (linear macromolecules), but most pharmaceutical grade materials do not meet the requirements. An improved technology based on FDM, called fused deposition of ceramics (FDC), gets rid of the limitations of materials used [ 7 ].…”
Section: 3d Printing Techniquesmentioning
confidence: 99%
“…Though most tissues and organs are structured with rich vascular networks, several studies indicated that the pro-vascularization of the dECM is not very promising [ 63 ]. Combining dECM bioinks with pro-angiogenic–related nanomaterials or drugs can effectively modulate the angiogenesis of recruited progenitor cells or embedded stem cells, and this phenomenon has also been demonstrated in other studies [ 155 , 156 ].…”
Section: Possible Challenges and Solutionsmentioning
confidence: 58%
“…However, it should be recognised that such printed or bioprinted implants could also be loaded with cells prior to implantation in a clinical setting and still be classified a print-and-implant strategy. Extensive reviews are available in the literature on cell sources for bone regeneration in general [23][24][25][26][27] and more specifically for bioprinting bone implants [9,10,[28][29][30][31][32][33][34][35].…”
Section: Print-and-implant Strategies That Harness Bone's Inherent Reparative Capacitymentioning
confidence: 99%